PROLIFIC CORN TEST UNIFORMITY TEST (COB TWO) - Maulidya Fachra Nisa Yusri; Irfan Suliansyah; Nalwida Rozen; Fitri Ekawati; Roza Yunita (JERAMI : Indonesian Journal of Crop Science, 2022)
One of the efforts that can be done is to increase the national corn productivity by developing prolific composite corn varieties. This is done because prolific corn is a type of corn with a tendency to produce two or more cobs, so that it can increase the value of corn production. The purpose of this study was to obtain prolific corn candidates (two cobs) with high yield and uniformity. This research was conducted using the mass selection method. Mass selection is done by selecting plants that have the desired character, namely prolific corn (cob two). The observed variables were the diversity in the F4 population, the percentage of prolific maize, and the comparison of the yield components of prolific maize with non-prolific maize. This study succeeded in obtaining 50% prolific corn on the cob and has wide diversity criteria. Of the 561 prolific corn plants, there are 91 corn plants that are classified as productive prolific. Prolific maize has a higher yield component than non-Prolific maize. Seed weight with cobs on productive prolific corn reached 318 g and seed weight reached 268 g.